2022
DOI: 10.1002/eji.202249841
|View full text |Cite
|
Sign up to set email alerts
|

Augmented neutralization of SARS‐CoV‐2 Omicron variant by boost vaccination and monoclonal antibodies

Abstract: Effective vaccines and monoclonal antibodies have been developed against coronavirus disease 2019 (COVID‐19) caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). However, the appearance of virus variants with higher transmissibility and pathogenicity is a major concern because of their potential to escape vaccines and clinically approved SARS‐CoV‐2‐ antibodies. Here, we use flow cytometry‐based binding and pseudotyped SARS‐CoV‐2 neutralization assays to determine the efficacy of boost immuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 37 publications
(50 reference statements)
1
18
0
Order By: Relevance
“…Of note, the epitopes of antibodies chosen here are in the NTD and RBD of the spike, the primary regions of variant mutations with effective neutralization evasion 5,62,63 . Impacted antibodies include STE90-C11, 4-8, S2M11, BD-368-2 by Omicron BA.1 62,64,65 and increased S309 escape by Omicron BA.2, BA.4/BA.5 63 . In the latter case, the loss of neutralization involves a region proximal to the N343 glycan, highlighting the important role of glycans in the immune response.…”
Section: /17mentioning
confidence: 99%
“…Of note, the epitopes of antibodies chosen here are in the NTD and RBD of the spike, the primary regions of variant mutations with effective neutralization evasion 5,62,63 . Impacted antibodies include STE90-C11, 4-8, S2M11, BD-368-2 by Omicron BA.1 62,64,65 and increased S309 escape by Omicron BA.2, BA.4/BA.5 63 . In the latter case, the loss of neutralization involves a region proximal to the N343 glycan, highlighting the important role of glycans in the immune response.…”
Section: /17mentioning
confidence: 99%
“…These Omicron sublineages share a subset of spike mutations but individually also contain unique spike mutations. 4 A single homologous vaccine boost after a primary series of either the BNT162b2 (Pfizer-BioNTech) or mRNA-1273 (Moderna) vaccines generates high titers of neutralizing antibodies to Omicron; [5][6][7] however, little is known about the durability of the response and the impact of heterologous vaccine boosting. As part of an ongoing study evaluating homologous and heterologous booster vaccines, 8 we assessed the magnitude and short-term durability of neutralizing activity against Omicron.…”
Section: Introductionmentioning
confidence: 99%
“…The exceptions included two studies in which the Omicron BA.1 sequence also contained A701V ( 9 , 14 ) and three studies in which the pseudotyped virus spike contained Q493K rather than Q493R ( 32 , 46 , 54 ). Several studies explicitly reported using pseudotyped viruses containing spike cytoplasmic tail truncations ( 16 , 23 , 32 , 36 , 42 , 54 ). This is a common practice used to increase the expression of spike proteins that may not have been consistently reported.…”
Section: Resultsmentioning
confidence: 99%